CONCENTRATION AND DISTRIBUTION OF POLYCYCLIC AROMATIC HIDROCARBONS (PAHs) DURING BIOREMEDIATION PROCESSES OF OIL-CONTAMINATED BEACH SEDIMENTS IN KARANG SONG BEACH, INDRAMAYU - Khozanah Khozanah; Dede Falahudin (BULLETIN OF THE MARINE GEOLOGY, 2016)
Bioremediation research was conducted from June to September, 2010 in oil-contaminated beach sediment in Karang Song Beach, Indramayu. The objective of this paper is to determine concentration and distribution of polycyclic aromatic hydrocarbon (PAH) during bioremediation processes. Upon 90 days biodegradation treatment, PAH concentration was reduced in several mesocosms. Concentration of PAH before treatment and after 90 day incubation were follows, Mesocosm A (110.499 mg/kg to 16.125 mg/kg),  Mesocosm B (217.067 mg/kg to  12.239 mg/kg),  Mesocosm C (102.016 mg/kg to  16.695 mg/kg), Mesocosm D (124.256 mg/kg to  60.869 mg/kg), Mesocosm E (117.723 mg/kg  to 50.663 mg/kg), Mesocosm F (143.495 mg/kg to 38.310 mg/kg), and Mesocosm G (9.838 mg/kg to 4.248 mg/kg). Generally, all mesocosms treatment  was reduced of PAH concentration, but there are no stable degraded after 60, and 90 days incubation. Fertilizer application has showed good influence for increasing degradation rate of bacteria to degraded oil contaminant. Keywords: polycyclic aromatic hydrocarbons (PAH), bioremediation, mesocosm, Karang Song, IndramayuPenelitian bioremediasi dilakukan dari Juni hingga September, 2010 di pantai Karang Song,  Indramayu yang sedimen telah  terkontaminasi minyak. Tujuan penelitian dari makalah ini adalah untuk mengamati konsentrasi dan distribusi Polisklik Aromatik Hidrokarbon (PAH) selama proses bioremediasi. Setelah 90 hari pengamatan biodegradasi, konsentrasi PAH dalam beberapa mesokosme menjadi menurun.. Konsentrasi PAH saat awal perlakuan dan setelah 90 hari inkubasi adalah sebagai berikut:, Mesokosme A (110,499 mg / kg menjadi 16,125 mg / kg), Mesokosme B (217,067 mg / kg menjadi 12,239 mg / kg), Mesokosme C (102,016 mg / kg menjadi 16,695 mg / kg), Mesokosme D (124,256 mg / kg menjadi sampai 60,869 mg / kg), Mesokosme E (117,723 mg / kg menjadi 50,663 mg / kg), Mesokosme F (143,495 mg / kg menjadi 38,310 mg / kg), dan Mesokosme G (9,838 mg / kg menjadi 4,248 mg / kg). Umumnya, semua pengobatan mesokosme menyebabkan berkurang konsentrasi PAH, tetapi tidak ada yang stabil terdegradasi setelah 60, dan 90 hari inkubasi. Pemupukan telah menunjukkan pengaruh yang baik untuk meningkatkan tingkat degradasi bakteri kontaminan minyak terdegradasi.Kata kunci: polycyclic aromatic hydrocarbons (PAH), bioremediasi, mesocosm, Karang Song, Indramayu